Macrolide Resistance in Mycoplasma genitalium in Singapore. (4th October 2017) - Barkham, Timothy; Tang, Wen Ying; Mansoor, Siti Aminah; Chio, Martin Tze-Wei
Abstract: Background: Mycoplasma genitalium was first reported as a cause of non-gonococcal urethritis in 1980. It has progressed from being an 'emerging' sexually transmitted infection (STI) to an accepted STI. Prevalence of infection has been reported as the Netherlands 4.5%, Sweden 6.3%, UK 1.2% and France 4%. M. genitalium has the smallest known bacterial genome and was the second bacterial genome fully sequenced. It has minimal requirements and is said to approach the minimum possible for a living cell. It is extremely fastidious; only a few strains have been cultured worldwide. Diagnosis relies on direct detection. It does not have a cell wall so it is not susceptible to antibiotics such as penicillins and cephalosporins. Therapy depends on fluoroquinolones and macrolides but resistance to macrolides has been widely reported: 13% France, 18% Sweden, 40% UK, Australia and Denmark, 100% Greenland, 30% Japan. Methods: Ethics approval was granted. DNA extracts left over after routine clinical diagnostics at the Department of STI Control (DSC) Clinic, Kelantan Lane, Singapore were harvested. DNA had been extracted on a Cobas 4800 instrument (Roche) from urine and urethral swabs collected for testing for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG). A 2-plex real-time PCR assay targeting the pdhD and mgpB genes was used to screen for M. genitalium . Samples were deemed positive if both targets were detected. If only one target was detected, the sample was retested; if reactive in either target upon retest, the sample was considered positive for M. genitalium . Positive DNA preps were then screened for macrolide resistance mutations after Sanger sequencing of the 23S rRNA gene. Results: 368 anonymised DNA elutes from 254 urines and 114 urethral swabs were collected between May and July 2016. One hundred eighty-four were CT/NG positive and 184 were CT/NG negative. Sixteen (4.3%) were positive for M. genitalium . Four (25%) of these 16 samples contained macrolide resistance associated mutations; A2058T (x2), A2058G (x1), and A2059G (x1). Conclusion: M. genitalium was detected in 4.3% of samples. Macrolide resistance mutations were detected in 25%, similar to international rates. Some guidelines recommend testing for resistance to guide therapy and to perform a test of cure. Disclosures: All authors: No reported disclosures.